Pola Migrasi dan Variabel yang Memengaruhinya di Provinsi Jawa Barat - Fauziyah, Syifa; Wijaya, Yuliagnis Transver (Seminar Nasional Official Statistics, 2024)
Migration is one of the demographic components of population growth in a region. A problem phenomenon in population growth that occurs at this time is that the population is not evenly distributed and only concentrated in one region. The purpose of this study is to determine the distribution pattern of migrant population working in the formal sector between districts / cities in West Java Province and the factors that influence it. This study uses multiple linear regression analysis methods to determine what variables affect the occurrence of migration, both in-migration, out-migration, and between the two that occur between districts / cities in West Java Province. The variables that significantly affect the occurrence of out-migration are the population size variable and the proportion of higher education; the variables that affect the occurrence of in-migration are the Gross Regional Domestic Product value variable and the proportion of higher education; the variables that affect migration between in-migration and out-migration include the neighboring variable, the stock of lifetime migrants, the GRDP ratio, and the distance ratio of the capital to the Province.